Effects of antenatal corticosteroids administration on fetoplacental circulation in preterm pregnancies with intrauterine growth restriction and its correlation with perinatal outcome - Choudhary, Neelima; Kesri, Ashima; Nain, Shilpi; Chaudhary, Vikas; Trivedi, S. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Antenatal corticosteroid administration in preterm pregnancies is recommended to promote fetal lung maturation. Studies have reported temporary reduction in fetal heart rate, breathing and movements following maternal corticosteroid administration. Authors studied effect of maternal corticosteroid administration on fetoplacental circulation in preterm pregnancies with IUGR and its correlation with perinatal outcome. Methods: Observational study included 77 preterm singleton pregnant women with IUGR. Color doppler day 0 (before betamethasone) of umbilical artery of 77 cases done. All received two doses of 12 mg of betamethasone intramuscularly 24 hours apart. Umbilical artery doppler on day 2 (24 to 48 hours of 1st dose of betamethasone) and day 4 (72 to 96 hours of 1st dose of betamethasone) done. Pulsatility index (PI) of umbilical artery on doppler and Neonatal details of all women noted. Results: On day 2 doppler, 56 (73%) women (Group A) showed decrease in umbilical artery PI while 21 (27%) women (Group B) did not show decrease in umbilical artery PI. Mean umbilical artery PI of 77 cases on day 0 and day 2 were 1.73±0.73 and 1.54±0.76 respectively (p<0.001). Mean Umbilical artery PI values of undelivered 60 cases on day 0, day 2 and day 4 were 1.55±0.61, 1.33±0.55 and 1.47±0.63 respectively (p<0.001). Group B neonates had poorer Apgar scores, higher neonatal complication, longer hospital stay, lesser umbilical pH at birth and higher perinatal mortality rate than Group A neonates. Conclusions: Significant reduction in mean umbilical artery PI observed on day 2 following betamethasone administration (p<0.001), which was maintained till 4th day after 1st dose of betamethasone (p<0.05). Women who showed improvement in umbilical artery pulsatility index following betamethasone administration had a better perinatal outcome as compared to women who did not.